2021
DOI: 10.3390/jox11030008
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Exposures to Perfluoroalkyl Substances and Diabetes, Hyperglycemia, or Insulin Resistance: A Scoping Review

Abstract: Per- and polyfluoroalkyl substances (PFASs) are persistent environmental pollutants that are commonly found in the human body due to exposures via drinking water, surfactants used in consumer materials, and aqueous film-forming foams (AFFFs). PFAS exposure has been linked to adverse health effects such as low infant birth weights, cancer, and endocrine disruption, though increasingly studies have demonstrated that they may perturb metabolic processes and contribute to dysfunction. This scoping review summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…Using an experimental mouse model of autoimmune diabetes, Bodin and co-workers showed that PFUnDA exposure of female mice from conception and up to 30 weeks of age exacerbated pancreatic insulitis development, a potential early marker for type 1 diabetes (T1D), but did not accelerate diabetes development [ 192 ]. A recent scoping review included three epidemiological studies examining associations between different PFAS and T1D, but no clear trends could be identified [ 193 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using an experimental mouse model of autoimmune diabetes, Bodin and co-workers showed that PFUnDA exposure of female mice from conception and up to 30 weeks of age exacerbated pancreatic insulitis development, a potential early marker for type 1 diabetes (T1D), but did not accelerate diabetes development [ 192 ]. A recent scoping review included three epidemiological studies examining associations between different PFAS and T1D, but no clear trends could be identified [ 193 ].…”
Section: Resultsmentioning
confidence: 99%
“…While there is strong evidence supporting the direct activation of PPARs, there is less evidence that PFAS directly activate endocrine receptors, including estrogen (ER) and androgen receptors (AR). Hence, the mechanism of endocrine disruption mediated by PFAS remains unclear, suggesting that indirect mechanisms, including epigenetic and/or metabolic reprogramming, may play roles in disrupting the production and secretion of endocrine hormones during critical windows of exposure [ 44 , 96 ] ( Figure 2 ). In turn, early-life exposure to EDCs has been associated with epigenetic reprogramming that manifests later in life [ 97 ].…”
Section: Potential Mechanisms Of Pfas Carcinogenesismentioning
confidence: 99%
“…PFAS have been associated with multiple chronic diseases in epidemiological studies including immunotoxicity, cardiometabolic disease, developmental and reproductive effects, and cancer (36)(37)(38)(39)(40). More recent studies have begun to explore associations between PFAS exposure and diabetes (14,15). However, the link between PFAS exposure and the development of diabetes continues to be a disputed area of study, with conflicting data having been reported from various epidemiological studies.…”
Section: Pfas and Glucose Homeostasismentioning
confidence: 99%
“…In addition, little physical activity, a poor diet, smoking, stress, and high body mass index have all been attributed in the promotion of T2D prevalence and incidence (10). However, studies have begun to investigate additional environmental factors that potentially impact on the development of diabetes, such as exposure to environmental contaminants acting as endocrine-disrupting chemicals, including per-and polyfluoroalkyl substances (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%